2016
DOI: 10.1021/acs.jproteome.5b01025
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Modeling To Monitor Host Responsiveness to Gut Microbiota Manipulation in the BTBRT+tf/j Mouse

Abstract: The microbiota, the entirety of microorganisms residing in the gut, is increasingly recognized as an environmental factor in the maintenance of health and the development of disease. The objective of this analysis was to model in vivo interactions between gut microbiota and both serum and liver metabolites. Different genotypic models (C57BL/6 and BTBR(T+tf/j) mice) were studied in combination with significant dietary manipulations (chow vs ketogenic diets) to perturb the gut microbiota. Diet rather than genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
(57 reference statements)
2
39
0
1
Order By: Relevance
“…The changes, or lack thereof, may reflect cell-intrinsic epigenetic or genetic programming, or other factors in the peripheral immune environment may also be necessary to produce neuro-immune alterations in behavior. Importantly, the characteristic low sociability in BTBR mice are hypothesized to emerge from a combination of changes in nervous system (Fenlon et al, 2015), gastrointestinal-microbiota (Klein et al, 2016), metabolic (Smith et al, 2016; Zilkha et al, 2016), and immunological function (Careaga et al, 2015b; Onore et al, 2013). This suggests there may be several factors working synergistically to modulate the social behavior improvements observed in BTBR-Allogeneic recipients and underscores the complex nature of social behavior deficits in the BTBR mouse strain.…”
Section: Discussionmentioning
confidence: 99%
“…The changes, or lack thereof, may reflect cell-intrinsic epigenetic or genetic programming, or other factors in the peripheral immune environment may also be necessary to produce neuro-immune alterations in behavior. Importantly, the characteristic low sociability in BTBR mice are hypothesized to emerge from a combination of changes in nervous system (Fenlon et al, 2015), gastrointestinal-microbiota (Klein et al, 2016), metabolic (Smith et al, 2016; Zilkha et al, 2016), and immunological function (Careaga et al, 2015b; Onore et al, 2013). This suggests there may be several factors working synergistically to modulate the social behavior improvements observed in BTBR-Allogeneic recipients and underscores the complex nature of social behavior deficits in the BTBR mouse strain.…”
Section: Discussionmentioning
confidence: 99%
“…Group-specific primers are shown in Additional file 1: Table S1 and referenced in previously published work [13]. All baseline animal and transformed gut microbiota data have been previously published [15], and they are included here to provide a frame of reference for the autism-related data. Previously published work examines the mathematical relationship between specific gut microbes and serum metabolomics and not ASD.…”
Section: Methodsmentioning
confidence: 99%
“…The KD has been shown to alter the composition of gut microbiota in mice and ketosis is associated with altered gut microbiota in humans [46,47,48,49]. Studies using two mouse models of epilepsy (6 Hz stimulation test and mice harboring a null mutation in the alpha subunit of voltage-gated potassium channel Kv1.1) demonstrate that KD induced changes in gut microbiota, produced by feeding or fecal transplant, are necessary and sufficient to confer seizure protection.…”
Section: Kds In the Management Of Adult Epilepsy And Refractory Sementioning
confidence: 99%
“…The effect appears to be mediated by select microbial interactions that reduce bacterial gamma-glutamylation activity, decrease peripheral gamma-glutamylated-amino acids and elevate bulk hippocampal GABA/glutamate ratios [50]. As rodent studies have shown different taxonomic shifts in response to KD therapy, the gut microbiota induced by KDs will depend on host genetics and baseline metabolic profiles [46,50]. Further research is needed to determine effects of the KD on microbiome profiles in adults with drug-resistant epilepsy and whether particular taxonomic changes in gut microbiota correlate with seizure severity and response to therapy.…”
Section: Kds In the Management Of Adult Epilepsy And Refractory Sementioning
confidence: 99%